2022
DOI: 10.1007/s12144-022-03994-z
|View full text |Cite
|
Sign up to set email alerts
|

Reduced vagal tone in intimate partner violence perpetrators is partly explained by anger rumination

Abstract: Polyvagal theory proposed that an autonomous nervous system imbalance might be characteristic of violent individuals, especially reduced parasympathetic or vagal tone. Accordingly, some studies concluded that when intimate partner violence (IPV) perpetrators deal with acute stress, they tend to present a sympathetic predominance over the parasympathetic nervous system once the stress has ended. However, less is known about cognitive mechanisms that explain this phenomenon. In fact, this functioning might be ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…Next, the Vrije Universiteit Ambulatory Monitoring System (VU‐AMS) psychophysiological device (specified later) was placed. Based on previous studies on emotional processing and IPV, a 5‐min baseline period was recorded (Behnke et al, 2022; Romero‐Martínez et al, 2022; Sarrate‐Costa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Next, the Vrije Universiteit Ambulatory Monitoring System (VU‐AMS) psychophysiological device (specified later) was placed. Based on previous studies on emotional processing and IPV, a 5‐min baseline period was recorded (Behnke et al, 2022; Romero‐Martínez et al, 2022; Sarrate‐Costa et al, 2022).…”
Section: Methodsmentioning
confidence: 99%
“…Regarding the second question, it is less clear whether or not increased vagal tone is reliably associated with increased antisocial behavior (Glenn & McCauley, 2019). A number of studies have found that reduced vagal tone is associated with increased antisocial behavior (Pang & Beauchaine, 2013;Sarrate-Costa, Lila, Comes-Fayos, Moya-Albiol, & Romero-Martinez, 2022). Similarly, one review of callous unemotional (CU) traits in children suggested that high CU scores are associated with reduced baseline vagal tone as measured by RSA (respiratory sinus arrythmia), while recognizing that only a handful of studies exist (Wagner & Waller, 2020).…”
Section: Introductionmentioning
confidence: 99%